2021
DOI: 10.22331/q-2021-09-07-536
|View full text |Cite
|
Sign up to set email alerts
|

On the experiment-friendly formulation of quantum backflow

Abstract: In its standard formulation, quantum backflow is a classically impossible phenomenon in which a free quantum particle in a positive-momentum state exhibits a negative probability current. Recently, Miller et al. [Quantum 5, 379 (2021)] have put forward a new, "experiment-friendly" formulation of quantum backflow that aims at extending the notion of quantum backflow to situations in which the particle's state may have both positive and negative momenta. Here, we investigate how the experiment-friendly formulati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…All such effects are therefore manifestations of the same mathematical phenomenon, seen through different coordinate systems. In the light of the recent interest in experimentally demonstrating quantum backflow [9][10][11][12][13] , we argue that projectile scenarios are more experimentally friendly and operationally interesting.…”
Section: Introductionmentioning
confidence: 94%
“…All such effects are therefore manifestations of the same mathematical phenomenon, seen through different coordinate systems. In the light of the recent interest in experimentally demonstrating quantum backflow [9][10][11][12][13] , we argue that projectile scenarios are more experimentally friendly and operationally interesting.…”
Section: Introductionmentioning
confidence: 94%
“…In this work the authors attempted to look at backflow when both positive and negative momentum eigenstates were present. This approach was commented on by Barbier and Goussev [22], who showed that this formulation and the standard one are not necessarily equivalent. Backflow has been observed theoretically in a PT symmetric ring which implies that it could be observed experimentally in such systems [23].…”
Section: Introductionmentioning
confidence: 99%
“…• BBA begin by questioning the statements by numerous authors, including us, that probability backflow is a 'peculiar quantum effect' [3], 'an intriguing quantum-mechanical phenomenon' [4], a 'surprising and clearly non-classical effect with no classical counterpart' [5], 'clearly a nonclassical effect' [6], 'a classically impossible phenomenon' [7], a 'new quantum effect' [8], and 'a generic purely quantum phenomenon' [9]. BBA suggest that these authors 'apparently have not read the paper by Berry [10] who has shown that the backflow effect also exist sic in simple one-dimensional situations in classical optics'.…”
Section: Introductionmentioning
confidence: 99%